International perspectives on the role of technology in humanizing higher education - Sengupta, Enakshi; Blessinger, Patrick; Makhanya, Mandla (Emerald Publishing Limited, 2020)
The debate around how to maximize the use of technology in education is ongoing, and embedded in the argument that successful inculcation of knowledge cannot happen only by improving the curriculum. But what role does technology play in humanizing higher education? How can it facilitate the kind of all-round development, beyond the classroom, which allows students to create a positive impact on social welfare and community wellbeing? The authors of this volume address the humaneness that surrounds the world of technology in education. By highlighting the use of emerging technologies in pedagogy and drawing on real-life case studies, they address the ongoing debate that technology brings a positive effect on education and beyond. More important than ever as mankind faces unprecedented challenges to classroom-based education, and the demand for technology grows, the authors demonstrate how technology continues to fulfil the challenges of creating a more democratic educational environment.
Prelims -- Part I: Creating Humanness with Technology -- Chapter 1: Introduction to International Perspectives on the Role of Technology in Humanizing Higher Education -- Chapter 2: Socially Present? The Perception of Humanness Online Through Video -- Chapter 3: The Role of the Teacher and AI in Education -- Chapter 4: Context-Based Projects: The Possibility of an Optimistic Learning Approach in the Technologically Enabled University -- Chapter 5: The Science and Technology of Educational Interconnectedness -- Part II: Emerging Technologies in Pedagogy -- Chapter 6: Enhancing the Role of the Hellenic Open University as a Lifelong Learning Organisation: Crossing the Rubicon into the E-Learning Era -- Chapter 7: Humanizing User Experience Design Strategies with NEW Technologies: AR, VR, MR, ZOOM, ALLY and AI to Support Student Engagement and Retention in Higher Education -- Chapter 8: Humanization of English Language Teaching through Computer-Assisted Language Learning in Turkish Tertiary Level English Preparatory Classes -- About the Authors -- Name Index -- Subject Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Education, Higher -- Effect of technological innovations on; Educational technology -- Social aspects; Education -- Higher; Colleges of further education